Lung function in sarcoidosis: An investigation of the disease as seen at a clinic in England and a comparison of the value of various lung function tests - Marshall, R. (1971)
A comprehensive series of lung function tests has been carried out on 130 patients with sarcoidosis. Selected results are presented but a full table of analysed results is obtainable on application to the authors. The results are discussed particularly in relation to patients with clear lung fields, to patients with bilateral hilar lymph node enlargement, and with regard to the choice of tests for repeated use in sarcoidosis patients.